Assessment Instrument Model for Natural Science Material Based on Research Findings and Quranic Verses: An Effort to Measure Students' Higher-Order Thinking Skills - Saregar, Antomi; Putra, Fredi Ganda; Anugrah, Adyt; Fitri, Megawati Ridwan (UIN Fatmawati Sukarno Bengkulu, 2024)
High-order thinking skills (HOTS) are essential abilities students must possess in the 21st Century. Understanding students' HOTS is crucial, necessitating measures to gauge the extent of their HOTS. This research aims to determine the feasibility and validity of a science assessment instrument based on integrated research results and Quranic verses. The researchers employed the R&D method with the ADDIE design. The validation was carried out by three material experts and three language experts. The assessment instrument was reliable and valid, had good discriminative power, and had a proportional difficulty level. It can be concluded that the assessment instrument is suitable for measuring students' higher-order thinking skills. This research provides a pioneering approach by integrating Al-Qur'an verses into the science assessment model, highlighting the intersection of religious texts and scientific methodologies. Additionally, the developed instrument measures higher-order thinking skills and offers educators a culturally relevant tool in predominantly Muslim educational settings, potentially enhancing students' engagement and comprehension. This integrative approach offers a fresh perspective on educational assessment tools, urging educators and curriculum developers to view religious texts as valuable resources in shaping contemporary educational paradigms